Ten- year comparison of two different techniques for femoral bone cavity preparation—broaching versus compaction in patients with cementless total hip arthroplasty. (2021) - Okowinski, M.; Hjorth, M. H.; Mosegaard, S. B.; JürgensLahnstein, J. H.; Jakobsen, S. Storgaard; Christensen, P. Hedevang; Kold, S.; Stilling, M.
No abstract available